Exploring the Impact of Confirmation, Perceived Usefulness, and Perceived Risk on User Satisfaction and Continuance Intention of Paylater Users - Freddy Pandapotan Simbolon; Eunice Klesia (Bina Nusantara University, 2024)
Financial service innovation is increasingly developing with the massive growth in the use of Information and Communication Technology (ICT). Paylater is a digital financial service product that has recently developed rapidly. Even though many people view paylater negatively, its presence is well-received, especially by young people. Paylater is a new trend in digital payment services, so there is still limited research that discusses the continuance intention of e-commerce users. The research aimed to determine the effect of confirmation, perceived usefulness, satisfaction, and perceived risk on continuance intention. The research, using a questionnaire and a quantitative approach, involved a sample of 209 users of paylater in Jakarta, which was taken through purposive sampling. The research tested hypotheses using the Structure Equation Modelling (SEM) model with the Partial Least Square (SEM-PLS). Research findings show that satisfaction and risk perception have a positive and significant effect on the intention to continue using paylater services. Confirmation and perceived usefulness are also found to positively and significantly influence satisfaction. Therefore, paylater service providers should be more innovative in providing attractive features. Then, paylater users need to improve their financial literacy to be wiser when using it. Last, service providers need a deep understanding to become leaders in providing paylater services, so conducting studies related to continuance intention is essential.